Teachers’ Perspectives on Teaching and Learning during the Pandemic in the United States - Ximena D. Burgin, Mayra C. Daniel, Teresa A. Wasonga (Educational Process: International Journal)
Background/purpose – As COVID-19 spread around the globe, learning was greatly impacted, with teachers having to pivot to remote delivery. This study documented teachers’ perceptions on the transition to online teaching and learning.